2010
DOI: 10.1673/031.010.18901
|View full text |Cite
|
Sign up to set email alerts
|

Identity of Two Sympatric Species ofOrius(Hemiptera: Heteroptera: Anthocoridae)

Abstract: The minute pirate bugs, Orius insidiosus (Say) and Orius pumilio (Champion) (Hemiptera: Heteroptera: Anthocoridae), are closely related species known to be sympatric in north Florida. Here, male and female genitalia, DNA sequences, and the effects of within- and between-species pairings on egg production and egg development were examined to develop a better understanding of the relationship between these two species. Interspecific matings between the two species did not result in viable progeny. Although there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
2
10
0
2
Order By: Relevance
“…In general, the relationship among different Orius species agreed with the previous constructed relationship (Honda et al 1998; Jung et al 2010; Shapiro et al 2010) with differences in the positions of some taxa in our tree. These differences could be because only the manually alignable fragment of ITS1 was used in the present study, whereas the previous studies used more data from ITS1 and aligned it automatically by Clustal W program.…”
Section: Resultssupporting
confidence: 89%
“…In general, the relationship among different Orius species agreed with the previous constructed relationship (Honda et al 1998; Jung et al 2010; Shapiro et al 2010) with differences in the positions of some taxa in our tree. These differences could be because only the manually alignable fragment of ITS1 was used in the present study, whereas the previous studies used more data from ITS1 and aligned it automatically by Clustal W program.…”
Section: Resultssupporting
confidence: 89%
“…Other recent studies confirmed the occurrence of TM in other taxa (e.g., flower bugs: Shapiro et al 2010;Tatarnic et al 2014). We propose that CW will be detected in many more taxa given that CWduring consensual sexual intercourse in humans was described only relatively recently.…”
Section: Cw Is Likely Understudied and Underreportedsupporting
confidence: 84%
“…This species is widely collected throughout much of North America east of the Rocky Mountains (Shapiro, Shirk, Kelley, Lewis, and Horton 2010), and is often a dominant foliar-dwelling predator in major field cropping systems such as corn (Isenhour and Marston 1981;Corey, Kambhampati, and Wilde 1998;Seagraves and Yeargan 2009), soybeans (Fox, Landis, Cardoso, and DiFonzo 2004;Rutledge, O'Neil, Fox, and Landis 2004), and alfalfa (Al-Deeb,…”
Section: Introductionmentioning
confidence: 99%